Local Banking Development and the Use of Debt Financing by New Firms. (November 2019) - Deloof, Marc; La Rocca, Maurizio; Vanacker, Tom
Abstract: We investigate the effects of local banking development on the debt financing of new firms using a large sample of Italian firms. Controlling for potential endogeneity issues, we find that new firms are more likely to use bank debt and have higher leverage in provinces with more bank branches relative to population. However, it is important to account for bank heterogeneity. For instance, more foreign banks in a province actually reduce access to bank debt. Taken together, our study provides new and nuanced evidence on the role of local banking development for the debt financing of new firms.